ПОКАЖЧИК ОСНОВНИХ ПУБЛІКАЦІЙ БРІОЛОГІВ УКРАЇНИ ЗА ОСТАННЄ ДЕСЯТИРІЧЧЯ (2001-2010 рр.) - Бойко, М.Ф.; Вірченко, В.М.; Лобачевська, О.В. (CHORNOMORSKI BOTANICAL JOURNAL, 2011)
ПОКАЖЧИК ОСНОВНИХ ПУБЛІКАЦІЙ БРІОЛОГІВ УКРАЇНИ ЗА ОСТАННЄ ДЕСЯТИРІЧЧЯ (2001-2010 рр.)